TOOLS OF ARTIFICIAL INTELLIGENCE IN PEDAGOGICAL ACTIVITY - Evgeniya V. Zhelnina; Natalia V. Lyubavina (Russian Studies in Culture and Society, 2024)
Background. The article is devoted to the topic of using artificial intelligence tools in teaching, which is relevant in the conditions of modern political and economic reality. The subject of the analysis is the factors influencing the teacher’s decision to use AI in his work.